Cladocoryne spongicola, a new species of tropical, sponge-associated athecate hydroid (Cnidaria: Hydrozoa) - Galea, Horia R.; Widiastuti, Widiastuti; Maggioni, Davide (Zootaxa, 2025)
A new species of Cladocoryne Rotch, 1871, C. spongicola sp. nov., a hydroid strictly associated to a host demosponge, is described from shallow waters in the NE of the island of Bali, Indonesia. Its cnidome lacks the distinctive elliptic macrobasic euryteles of the substrate generalist C. haddoni Kirkpatrick, 1890, retaining only the elongate counterpart, common to most species of the genus. Its gonophores are eumedusoids with four marginal bulbs, a canal system, and four basal interradial nematocyst pads. A morphological comparison with its congeners is provided. A multilocus (16S, 18S, 28S rRNA and COI) phylogenetic analysis confirms its divergence from C. floccosa Rotch, 1871 and C. haddoni, two of its congeners for which sequence data are available so far.